2022
DOI: 10.1080/15384047.2022.2072164
|View full text |Cite
|
Sign up to set email alerts
|

CAFs-derived small extracellular vesicles circN4BP2L2 promotes proliferation and metastasis of colorectal cancer via miR-664b-3p/HMGB3 pathway

Abstract: Our previous research has demonstrated that colorectal cancer (CRC) progression was promoted by circN4BP2L2. This study aimed to further explore the mechanism of circN4BP2L2 in the development of CRC from the perspective of small extracellular vesicles (sEVs). Cancer-associated fibroblasts cell (CAFs) and normal fibroblasts cell (NFs) were isolated from CRC tissues and adjacent tissues, respectively. The ultra-centrifugation was used for extraction of their related sEVs. Cell proliferation and apoptosis were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…EVs derived from adipocytes and adipose-endothelial cells were found to induce proliferation, migration and invasion of the recipient prostate cancer cells, thereby promoting metastasis in prostate cancer ( 64 , 65 ). While CAFs were found to support the surrounding tumor cells by transferring tumor-supportive signals via EVs, thereby contributing to tumor growth and metastasis in several cancer types ( 62 , 66 68 ). In addition, endothelial cell derived-EVs were shown to affect macrophages, by converting them to a M2-like phenotype thereby inducing an immunosuppressive environment and aiding in cancer progression ( 69 ).…”
Section: Tumor Derived Evsmentioning
confidence: 99%
“…EVs derived from adipocytes and adipose-endothelial cells were found to induce proliferation, migration and invasion of the recipient prostate cancer cells, thereby promoting metastasis in prostate cancer ( 64 , 65 ). While CAFs were found to support the surrounding tumor cells by transferring tumor-supportive signals via EVs, thereby contributing to tumor growth and metastasis in several cancer types ( 62 , 66 68 ). In addition, endothelial cell derived-EVs were shown to affect macrophages, by converting them to a M2-like phenotype thereby inducing an immunosuppressive environment and aiding in cancer progression ( 69 ).…”
Section: Tumor Derived Evsmentioning
confidence: 99%
“…Currently, a substantial body of research has illuminated the role of CAFs in the initiation and progression of cancers through the regulation of apoptosis. In colorectal cancer (CRC), the exosomes transport miRNAs (miR-224-5p [ 80 ], miR-181b-3p [ 81 ], and miR-135b-5p [ 82 ]) and circRNAs (circN4BP2L2 [ 83 ] and circSLC7A6 [ 84 ]) from CAFs into cancer cells to act as inhibitors of apoptosis and promote the pathogenesis of CRC. Moreover, the secretion of IL-6 by CAFs leads to the upregulation of BCL-XL and MCL-1 in CRC cells via the IL-6/STAT3 signaling pathway, which simultaneously promotes apoptosis resistance [ 85 ]; however, the dynamic interactions between pro-apoptotic and anti-apoptotic BCL‑2 protein families (BCL-2, BCL-XL, BCL-w, MCL-1 and BCL-2A1) balance the commitment of cells to apoptosis [ 86 , 87 ].…”
Section: Effects Of Cafs On Tumor Apoptosismentioning
confidence: 99%
“…Prior study has shown that treatment of CRC cells with exosomes derived from CAFs promotes cell proliferation, migration, tube-forming ability and inhibits apoptosis of CRC cells. The results of mechanistic experiments showed that CAFs could deliver circN4BP2L2 to CRC cells through secreted exosomes and inhibit CRC cell proliferation and migration by regulating the miR-664b-3p/HMGB3 pathway ( 121 ). There’s a significant increase in SNHG3 expression in CRC cells and CAFs-derived exosomes, while incubation of CRC cells using CAFs-EVs facilitated cell proliferation.…”
Section: Effect Of Cafs-derived Exosomal Ncrnas On Crc Cellsmentioning
confidence: 99%